Regional Seminar on Private Sector Participation and Irrigation Expansion in sub-Saharan Africa (2) - Hilmy, Sally; Abernethy, Charles L. (International Water Management Institute, 2002)
The context for irrigation development in Africa has been changing rapidly and drastically over the past decade. On the one hand, there is increasing scepticism about the returns to public investment in irrigation development, and a resulting decline in s